Spectrum of Hyperaldosteronism, Opportunities for Diagnosis - Jan Zeman; Karel Pacak; Gonzalo J. Acosta; Hans K. Ghayee; Mohamad Anas Sukkari (Annals of Internal Medicine: Clinical Cases)
Primary aldosteronism (PA) is a common cause of secondary hypertension. It is characterized by renin-independent overproduction of aldosterone by the adrenal glands. Recent data indicate higher prevalence of PA than previously thought. The clinical presentation varies depending on the severity of aldosterone hypersecretion. Several studies suggest that PA manifests as a continuous spectrum. We present 2 clinical scenarios that highlight the challenges clinicians face while interpreting the biochemical work-up for PA. We emphasize the importance of understanding the pathophysiology of PA while interpreting borderline results. The aim is to underscore the importance of early recognition and treatment of PA, which can improve outcomes.